Fatores críticos de sucesso para gerenciamento do conhecimento em indústrias inseridas no contexto digital e de inovação - Bochnia, Luis Fernando (2024)
The digitalization process of the industry has brought more than just digital tools but also updated forms of advanced Knowledge Management. The most important aspects of digital transformation for industries were the digitalization of processes, the Database, Artificial Intelligence (AI) Tools, Machine Learning, Internet of Things and other digital technologies. In line with this evolution, Knowledge in industries is becoming increasingly essential to reduce training costs and generate ideas that will be organized and archived or lost. The definition of critical success factors in knowledge management will benefit companies in prioritizing and guide industry managers on how to retain this knowledge using the tools of the Transforming Industry for the digital age. Therefore, the general objective of this work is to propose a prioritization model for the critical success factors of industrial knowledge management in the context of digital transformation. A literature review will be carried out using the PRISMA methodology to select articles extracted mainly from the Scopus and Web of Science databases. As partial results of this research, 89 articles were obtained in the final portfolio and with the use of the Nvivo tool, the main technological tools of the industry in digital transformation and the critical success factors in the implementation of knowledge management in the industry were found. From the survey of the critical success factors found in literature and the tools of the industry in digital transformation, a questionnaire will be developed, which will be based on the literature from the systematic review, to be sent to several expert managers in the industry who, after compiling the data, will be applied to a Fuzzy-DELPHI strategic management tool. This work will contribute to both Academia and industries, since the application of a Knowledge Management method within the industry undergoing digital transformation develops the best ways to retain knowledge and use it for the purpose of strengthening processes and reducing training and consulting costs, thus being a tool that systemically organizes the main characteristics called Critical Success Factors, in addition to guiding managers in decision-making and thus supporting the development of industries inserted in the context of digital transformation that calls for digital tools that result in knowledge retention.